Why is SARS-CoV-2 infection more severe in obese men? The gut lymphatics – Lung axis hypothesis. (November 2020) - Uzzan, Mathieu; Corcos, Olivier; Martin, Jerome C.; Treton, Xavier; Bouhnik, Yoram
Abstract: Consistent observations report increased severity of SARS-CoV-2 infection in overweight men with cardiovascular factors. As the visceral fat possesses an intense immune activity, is involved in metabolic syndrome and is at the crossroad between the intestines, the systemic circulation and the lung, we hypothesized that it plays a major role in severe forms of SARS-CoV-2 infection. SARS-CoV2 presents the ability to infect epithelial cells of the respiratory tract as well as the intestinal tract. Several factors may increase intestinal permeability including direct enterocyte damage by SARS-CoV2, systemic inflammatory response syndrome (SIRS) and epithelial ischemia secondary to SARS-CoV2- associated endothelial dysfunction. This increase permeability further leads to translocation of microbial components such as MAMPs (microbial-associated molecular pattern), triggering an inflammatory immune response by TLR-expressing cells of the mesentery fat (mostly macrophages and adipocytes). The pro-inflammatory cytokines produced by the mesentery fat mediates systemic inflammation and aggravate acute respiratory distress syndrome (ARDS) through the mesenteric lymph drainage.